(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the different categories of Modus and their meanings to study the concept of modality. It is noted that the category “modus” is much wider than the category “modality”. This is due to the fact that modus is divided into three categories: actualization, qualification and social. The modality, on the other hand, belongs to the actualization category of the modus.